Fibrinolysis and Remote Ischemic Conditioning: Mechanisms and Treatment Perspectives in Stroke - Krag, Andreas Engel; Blauenfeldt, Rolf Ankerlund (Seminars in Thrombosis and Hemostasis, 2021)
Stroke is a leading cause of death and disability. Intravenous thrombolysis and mechanical thrombectomy have greatly improved outcomes in acute ischemic stroke (AIS). However, only a minority of patients receive reperfusion therapies, highlighting the need for novel neuroprotective therapies. Remote ischemic conditioning (RIC), consisting of brief, intermittent extremity occlusion and reperfusion induced with an inflatable cuff, is a potential neuroprotective therapy in acute stroke. The objective of this narrative review is to describe the effect of RIC on endogenous fibrinolysis and, from this perspective, investigate the potential of RIC in the prevention and treatment of stroke. A systematic literature search was performed in PubMed, and human studies in English were included. Seven studies had investigated the effect of RIC on fibrinolysis in humans. Long-term daily administration of RIC increased endogenous fibrinolysis, whereas a single RIC treatment did not acutely influence endogenous fibrinolysis. Fifteen studies had investigated the effect of RIC as a neuroprotective therapy in the prevention and treatment of stroke. Long-term RIC administration proved effective in reducing new cerebral vascular lesions in patients with established cerebrovascular disease. In patients with acute stroke, RIC was safe and feasible, though its clinical efficacy as a neuroprotectant is yet unproven. In conclusion, a single RIC treatment does not affect fibrinolysis in the acute phase, whereas long-term RIC administration may increase endogenous fibrinolysis. Increased endogenous fibrinolysis is unlikely to be the mediator of the acute neuroprotective effect of RIC in stroke patients, whereas it may partly explain the reduced stroke recurrence associated with long-term RIC treatment.
Keywords: fibrinolysis; ischemic preconditioning; stroke; cerebral hemorrhage; intracranial arteriosclerosis